INVENTARISASI KERUSAKAN DAN STRATEGI REHABILITASI HUTAN MANGROVE DI DESA KEERA KECAMATAN KEERA KABUPATEN WAJO - Mappanganro, Fadliah; Asbar, Asbar; Danial, Danial (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to assess the level of damage and factors causing damage to mangrove ecosystems in Keera Village Keera District Wajo and formulate rehabilitation strategies in the management of mangrove ecosystem that has not been right. The results showed that mangrovr closure conditions in coastal areas of Keera Village were in moderate category (mean percentage of highest closure type Rhizopora apiculata 62,5%). The results of image interpretation also showed a reduction of mangrove forest area by Â± 28,15 Ha from year 2013-2017. Damage to mangrove ecosystem is caused by conversion of mangrove land to be used as a pond and abrasion area due to lack of public understanding on the importance of conservation of mangrove ecosystem. The direction of the mangrove forest rehabilitation strategy in Keera Village based on the SWOT analysis is determined 8 strategies, namely: 1) Restoring mangrove function in accordance with ecological space rehabilitation pattern; 2) the procurement of mangrove cultivation facilities (nurseries and seeding) that are directly managed by the community; 3) improving the quality of community human resources around the mangrove ecosystem; 4) Improving the main tasks of community groups of supervisors through operational assistance; 5) law enforcement and institutional strengthening; 6) Replanting of identified mangrove coastal areas is severely damaged by abrasion; 7) increasing community participation and other stakeholders in the rehabilitation of mangrove ecosystems; 8) development of a good pond-based system (silvofishery).